Comparison of the effects of ringer’s lactate and stereofundin ISO solutions on acid base balance, electrolyte status and stress response in complex reconstructive micro-surgery patients - Tajudin, Mohd Suhaimi (2014)
Introduction: The beneficial effects of unbalanced crystalloid, normal isotonic 0.9% saline, have been sullied by many undesirable complications such as metabolic acidosis, serious biochemical abnormalities and other systemic side effects. However, the introduction of balanced crystalloids, sterofundin and Hartmann’s solution, provides a resolution to such problems. Nevertheless no studies have been conducted so far to directly compare the efficacy of two different balanced crystalloids with respect to protection against acid base, biochemical and stress response derangements up to 24 hours post infusion in surgical setting. Objectives: The aims of this study were to determine any significant differences in acid base balance, electrolyte profiles and stress response between patients on sterofundin and Hartmann’s solution following reconstructive microsurgery. Patients and Methods: A randomized single centre, single blind, two parallel groups, controlled trial was conducted in HUSM between November 2013 and February 2014. A total of 60 reconstructive microsurgical subjects were recruited and randomized in 1:1 ratio into two groups using block randomization. Blood was sampled at baseline, 5 hours after infusion, and 24 hours post infusion and standard fluid management protocols were followed. The primary outcome measures were mean changes in acid-base balance parameters (pH, bicarbonate levels, anion gap, base excess and aSID), serum biochemistry (urea and other electrolytes) and stress response (serum cortisol) from baseline to 24 hours after infusion. Repeated measure ANOVA was employed as a mean of statistical analysis. Results: Sterofundin recipients required a significant lesser amount of fluid volume than Hartmann’s solution group. Based on trend analysis of the data, Sterofundin recipients showed a greater rebound of pH and lesser declines in anion gap and aSID than Hartmann recipients at 24 hours. Sterofundin was also more effective than Hartmann’s solution in preventing major derangements and fluctuations of the majority of mean serum electrolytes (chloride, magnesium, calcium) and urea. On the other hand, Hartmann’s solution showed greater capacity in preserving mean serum osmolarity. With respect to stress response, Hartmann’s solution mitigated the raise in serum cortisol within the first 5 hours post infusion whilst Sterofundin caused a greater resolution of stress response at the end of 24 hour followup. Conclusion: Sterofundin showed greater capacity in preserving acid-base balance, biochemical profiles and stress response than Hartmann’s solution.